Clinical value of human epididymis protein 4 and the Risk of Ovarian Malignancy Algorithm in differentiating borderline pelvic tumors from epithelial ovarian cancer in early stages. (November 2015) - Kotowicz, Beata; Fuksiewicz, Malgorzata; Sobiczewski, Piotr; Spiewankiewicz, Beata; Jonska-Gmyrek, Joanna; Skrzypczak, Maciej; Kowalska, Maria
Abstract: Objective: The clinical value of human epididymis protein 4 (HE4) and the possibility of its use in the differential diagnosis in patients with benign, borderline and epithelial ovarian cancer in early International Federation of Gynaecology and Obstetrics (FIGO) stages. Study design: The study group consisted of 205 women, including 60 with ovarian cancer, 18 with borderline tumors, 77 with benign lesions and 50 healthy subjects. In all the patients, before the treatment and in control groups, we determined CA 125 and HE4 in serum by electrochemiluminescence on the basis of the COBAS e601 system. For comparison of two independent groups, we used the U Mann–Whitney test. The analysis of the diagnostic power of the assessed parameters has been determined using the MedCalc statistical program. The probability of disease free survival (DFS) was evaluated using the log-rank test and Cox regression model. Results: Concentrations of HE4, CA 125 and Risk of Ovarian Malignancy Algorithm (ROMA) value were significantly higher in early ovarian cancer than in patients with benign ( P < 0.0001) and borderline tumors ( P < 0.002), the receiver operating characteristics (ROC) curves, demonstrated the highest diagnostic sensitivity for the ROMA score, as well post (AUC = 0.817) as pre-menopausal (AUC = 0.806). HE4 concentrations ( P < 0.021) and the value of the ROMA score ( P < 0.004) were significantly higher in patients with relapse than in patients in remission. There was no connection between concentrations of the studied tumor markers and DFS. Conclusions: Determination of HE4 serum concentrations has a significant clinical value, especially in patients with benign lesions and elevated CA 125 levels. The combined assessment of HE4, CA 125 and the ROMA algorithm is helpful in differentiating benign tumors and borderline pelvic tumors from epithelial ovarian cancer in early FIGO stages. Determination of HE4, CA 125 and ROMA algorithm is not helpful in differentiating patients with borderline from benign lesions.